Victim Impact Statements for Equitable Judicial Protection of Crime Victims - Bambang Prayitno; Angkasa Angkasa; Kuat Puji Prayitno; Budiyono Budiyono; Mohd Shafiee Bin Hamzah (Journal of Human Rights, Culture and Legal System, 2026)
Indonesia's criminal justice system prioritizes offender prosecution while Law Number 20 of 2025 introduces Victim Impact Statements to strengthen victims' rights. However, the law does not clearly regulate its substantive content, legal function, procedural mechanism, or influence on judicial decision making. This study examines the implementation of the Victim Impact Statement in the Indonesian criminal justice system, evaluates its role in strengthening legal protection for victims, and formulates an ideal integration model. The research employs an empirical legal method using statutory, case, conceptual, and comparative approaches with qualitative analysis of interviews, documents, and legal materials. The findings produce three principal conclusions. First, the existing legal framework does not comprehensively integrate the Victim Impact Statement into the Indonesian criminal justice process, resulting in inconsistent implementation and limited legal effectiveness. Second, the absence of clear substantive and procedural standards restricts judges from incorporating the Victim Impact Statement effectively into sentencing considerations and limits its contribution to victim protection. Third, Indonesia needs to establish a comprehensive normative and procedural framework that strengthens the legal position of victims, supports informed judicial decision making, promotes balanced participation between victims and offenders, and advances a more equitable and justice oriented criminal justice system